Caenorhabditis elegans: a model to investigate oxidative stress and metal dyshomeostasis in Parkinson's disease - Chege, Patricia M.; McColl, Gawain (Frontiers in Aging Neuroscience, 2014)
Parkinson's disease (PD) is characterized by progressive motor impairment attributed to progressive loss of dopaminergic (DAergic) neurons in the substantia nigra pars compacta. Additional clinical manifestations include non-motor symptoms such as insomnia, depression, psychosis, and cognitive impairment. PD patients with mild cognitive impairment have an increased risk of developing dementia. The affected brain regions also show perturbed metal ion levels, primarily iron. These observations have led to speculation that metal ion dyshomeostasis plays a key role in the neuronal death of this disease. However, the mechanisms underlying this metal-associated neurodegeneration have yet to be completely elucidated. Mammalian models have traditionally been used to investigate PD pathogenesis. However, alternate animal models are also being adopted, bringing to bear their respective experimental advantage. The nematode, Caenorhabditis elegans, is one such system that has well-developed genetics, is amenable to transgenesis and has relatively low associated experimental costs. C. elegans has a well characterized neuronal network that includes a simple DAergic system. In this review we will discuss mechanisms thought to underlie PD and the use of C. elegans to investigate these processes.